Etika dan Tanggung Jawab Sosial dalam Bisnis Digital di Era Generasi Z - Rushel Hardi; Riswan Rambe (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to investigate how Generation Z applies social responsibility and corporate ethics in the setting of digital business. This research uses academic journals, scholarly articles, and pertinent books as its primary sources and employs a descriptive qualitative methodology using a literature review method. According to the research, Generation Z has a tendency to include moral principles like justice, openness, and honesty into their online company operations. Furthermore, Generation Z exhibits a high degree of social consciousness through more adaptable and values-based forms of social responsibility, like community empowerment and environmental advocacy. According to these results, Generation Z introduces a new paradigm to the digital business world, combining social concern, ethics, and technology to develop more ethical and sustainable company models.